Improvement of solubility, dissolution, and bioavailability of phenytoin intercalated in Mg-Al layered double hydroxide - Anwar Bakr, Rehab; Kotta, Sabna; Aldawsari, Hibah Mubarak; Ashri, Lubna Y.; Badr-Eldin, Shaimaa M.; Eltahir, Heba; Ahmed, Sameh A.; Alahmadi, Yaser M.; Abouzied, Mekky (Frontiers in Pharmacology, 2024)
Layered double hydroxides (LDHs) are highly effective drug delivery systems, owing to their capacity to intercalate or adsorb biomaterials, flexible structure, swelling property, high stability, good biocompatibility, and ease of synthesis. Phenytoin (PHT) is an antiseizure BCS (Biopharmaceutics Classification System) class II drug, presenting low aqueous solubility. Therefore, the current study aimed at increasing its solubility, dissolution, and bioavailability. PHT was intercalated to the MgAl-LDH formed in situ and successful intercalation to form MgAl-PHT-LDH was confirmed by FTIR, PXRD, DSC, and TGA. Examination of particle size and morphology (by photon correlation spectroscopy and electron microscopy, respectively) confirmed the formation and intercalation of nanostructured LDH. Intercalation enhanced the saturation solubility of PHT at 25ºC in 0.1N HCl and phosphate buffer (pH 6.8) by 6.57 and 10.5 times respectively. The selected drug excipient powder blend for the formulation of MgAl-PHT-LDH tablets exhibited satisfactory properties in both precompression parameters (angle of repose, bulk density, tapped density, Carr's index, and Hausner ratio) and tablet characteristics (weight variation, thickness, hardness, friability, content uniformity, and disintegration time). MgAl-PHT-LDH tablets showed better dissolution of PHT compared to unprocessed PHT tablets at all time points. Oral bioavailability of MgAl-PHT-LDH tablets and unprocessed PHT tablets was tested in two groups of Sprague Dawley rats based on analysis of serum levels of both forms of PHT by UPLC-ESI-MS/MS serum. MgAl-PHT-LDH tablets demonstrated a relative bioavailability of 130.15% compared to unprocessed PHT tablets, confirming a significantly higher oral bioavailability of MgAl-PHT-LDH. In conclusion, MgAl-PHT-LDH could provide a strategy for enhancing solubility, dissolution, and thereby bioavailability of PHT, enabling the evaluation of theclinical efficacy of MgAl-PHT-LDH tablets for the treatment of seizures at lower PHT doses.